Traits Without Borders: Integrating Functional Diversity Across Scales - Carmona, Carlos P; de Bello, Francesco; Mason, Norman W H; Lepš, Jan (Trends in ecology & evolution, 2016)
Owing to the conceptual complexity of functional diversity (FD), a multitude of different methods are available for measuring it, with most being operational at only a small range of spatial scales. This causes uncertainty in ecological interpretations and limits the potential to generalize findings across studies or compare patterns across scales. We solve this problem by providing a unified framework expanding on and integrating existing approaches. The framework, based on trait probability density (TPD), is the first to fully implement the Hutchinsonian concept of the niche as a probabilistic hypervolume in estimating FD. This novel approach could revolutionize FD-based research by allowing quantification of the various FD components from organismal to macroecological scales, and allowing seamless transitions between scales.
Keywords: Models, Biological; Phenotype; Ecology; pravděpodobnost; fenotyp; Ecosystem; ekosystém; Probability; biologické modely; ekologie